Vancomycin efficiency and safety of a dosage of 40–60 mg/kg/d and corresponding trough concentrations in children with Gram-positive bacterial sepsis - Peng, Lengyue; Guo, Ziyao; Zhang, Guangli; Tian, Xiaoyin; Gu, Ruixue; Li, Qinyuan; Li, Yuanyuan; Luo, Zhengxiu (Frontiers in Cellular and Infection Microbiology, 2023)
Background Optimal vancomycin trough concentrations and dosages remain controversial in sepsis children. We aim to investigate vancomycin treatment outcomes with a dosage of 40-60 mg/kg/d and corresponding trough concentrations in children with Gram-positive bacterial sepsis from a clinical perspective. Methods Children diagnosed with Gram-positive bacterial sepsis and received intravenous vancomycin therapy between January 2017 and June 2020 were enrolled retrospectively. Patients were categorized as success and failure groups according to treatment outcomes. Laboratory, microbiological, and clinical data were collected. The risk factors for treatment failure were analyzed by logistic regression. Results In total, 186 children were included, of whom 167 (89.8%) were enrolled in the success group and 19 (10.2%) in the failure group. The initial and mean vancomycin daily doses in failure group were significantly higher than those in success group [56.9 (IQR =42.1-60.0) vs. 40.5 (IQR =40.0-57.1), P=0.016; 57.0 (IQR =45.8-60.0) vs. 50.0 (IQR =40.0-57.6) mg/kg/d, P=0.012, respectively] and median vancomycin trough concentrations were similar between two groups [6.9 (4.0-12.1) vs.7.3 (4.5-10.6) mg/L, P=0.568)]. Moreover, there was no significant differences in treatment success rate between vancomycin trough concentrations ≤15 mg/L and >15 mg/L (91.2% vs. 75.0%, P=0.064). No vancomycin-related nephrotoxicity adverse effects occurred among all enrolled patients. Multivariate analysis revealed that a PRISM III score ≥10 (OR =15.011; 95% CI: 3.937-57.230; P<0.001) was the only independent clinical factor associated with increased incidence of treatment failure. Conclusions Vancomycin dosages of 40-60 mg/kg/d are effective and have no vancomycin-related nephrotoxicity adverse effects in children with Gram-positive bacterial sepsis. Vancomycin trough concentrations >15 mg/L are not an essential target for these Gram-positive bacterial sepsis patients. PRISM III scores ≥10 may serve as an independent risk factor for vancomycin treatment failure in these patients.